Corporate Governance, Political Connection, Family Ownership and Tax Aggressiveness in Indonesia - Setyastrini, Ni Luh Putri; Subekti, Imam; Prastiwi, Arum (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022), 2022)
Tax aggressiveness is a strategy of companies to present lower taxable earnings through tax planning without being accused of committing tax fraud, hence considered as one of the weaknesses of the self-assessment system. The purpose of this study was to examine and analyze the effect of corporate governance and political connection on tax aggressiveness with family ownership as the moderator. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. Using purposive sampling method, 49 companies were selected as the sample, resulting in 245 observations. The data were analyzed using multiple regression analysis and moderated regression analysis. This study found that corporate governance does not influence tax aggressiveness, that political connection has a negative effect on tax aggressiveness, and that family ownership does not moderate the influence of corporate governance and political connection on tax aggressiveness. Keywords:  tax aggressiveness, corporate governance, political connection, family ownership